2007
DOI: 10.1152/japplphysiol.01166.2006
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral impairments cause a progressive age-related loss of strength and velocity-dependent power in the dorsiflexors

Abstract: Muscle power is more functionally relevant than static muscle strength, particularly with aging. However, the effect of age on power derived from isotonic contractions has been studied sparingly, and it has not been studied at all in subjects >75 yr of age. Thus the purpose was to investigate the magnitude and causes of age-related losses in isotonic power among 13 young (26 yr), 13 old (65 yr), and 13 very old (84 yr) men. Six different loads were employed to create velocity-torque and power-torque relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
72
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 34 publications
(87 reference statements)
11
72
1
1
Order By: Relevance
“…Thus, at the whole muscle level, in the present study, both old groups were weaker but the intrinsic contractile properties of the contractile muscle mass, at least for torque generation, appears to be essentially intact. In contrast, McNeil et al (2007) found a decrease in normalized strength in their very old age group of men who were older (~5 years) than the upper age group of men in our study. In that prior study, the very old men were found to have decreased strength values, but not significantly different muscle CSA which accounted for the difference Fig.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Thus, at the whole muscle level, in the present study, both old groups were weaker but the intrinsic contractile properties of the contractile muscle mass, at least for torque generation, appears to be essentially intact. In contrast, McNeil et al (2007) found a decrease in normalized strength in their very old age group of men who were older (~5 years) than the upper age group of men in our study. In that prior study, the very old men were found to have decreased strength values, but not significantly different muscle CSA which accounted for the difference Fig.…”
Section: Discussioncontrasting
confidence: 97%
“…4), Schwenzer et al (2009) reported 6 % lower MTR values for healthy old (~65 years) versus young participants in the TA. Thus, MTR may be a sensitive measure of MQ and the functional declines to follow, as MTR depicts a decrease in MPQ in the eighth decade of life, but a decrease in normalized strength was not found in this muscle until the ninth decade of life (McNeil et al 2007). Results from the present study also highlight that sarcopenia cannot be explained by a single process but is the result of a number of contributing factors that perhaps converge due to reduced compensatory abilities in each factor by the eighth decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the major secondary findings was an age-related decrease of maximal torque which achieved statistical significance in men but just failed to do so in women (P 00.06). For both sexes, elbow flexor strength was reasonably wellmaintained until the eighth decade at which point it began to decline somewhat rapidly (Table 2), which is similar to previous findings of other muscle groups (e.g., Kallman et al 1990;McNeil et al 2007;Vandervoort and McComas 1986). Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The age-related decline in motor function (Enoka et al 2003;McNeil et al 2007;Nardone et al 1995;Stelmach et al 1989;Woollacott 1998, 1999) is not only associated with alterations affecting the muscular (McNeil et al 2007) but also the neural system (Enoka et al 2003). During voluntary contractions and responses to sudden perturbations of a limb or whole body, motor neurone activity is modulated by both the descending input and sensory feedback (Nielsen 2004).…”
Section: Introductionmentioning
confidence: 99%